2016
DOI: 10.4103/0974-2727.176232
|View full text |Cite
|
Sign up to set email alerts
|

An Audit of Requests for Fresh Frozen Plasma in a Tertiary Care Center in South India

Abstract: Aim:To audit the fresh frozen plasma (FFP) usage with an insight into various guidelines.Materials and Methods:The blood bank records pertaining to FFP usage in patients admitted in our medical college hospital were retrospectively reviewed for 2 years for usage of FFP in various departments and evaluated for appropriateness of usage based on various guidelines, which included the 2013 guidelines published by the National Health and Medical Research Council and the Australasian Society for Blood Transfusion.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…In the same study, the indication of the reversal of oral anticoagulant effect without bleeding was shown to be the rarest reason for improper FFP use, which is inconsistent with the results of our study 2 . Similarly, in a study by Pahuja et al and in another one by Lingegowda et al, it was reported that no improper FFP use was seen to reverse warfarin effect in their patient groups 6, 11. The hospital where our study was conducted is located in a densely populated area of settlement where the elderly are many in number; most of those who apply to the emergency department were of geriatric patient population.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In the same study, the indication of the reversal of oral anticoagulant effect without bleeding was shown to be the rarest reason for improper FFP use, which is inconsistent with the results of our study 2 . Similarly, in a study by Pahuja et al and in another one by Lingegowda et al, it was reported that no improper FFP use was seen to reverse warfarin effect in their patient groups 6, 11. The hospital where our study was conducted is located in a densely populated area of settlement where the elderly are many in number; most of those who apply to the emergency department were of geriatric patient population.…”
Section: Discussionsupporting
confidence: 60%
“…determined the improper use of FFP to be 45% in Canada, whereas, in Asian and European countries, the use of FFP with an improper indication ranged from 21% to 78% 2, 4, 6, 11, 12. In a study conducted in our country by Akkaş et al, the rate of improper use was found to be 67%, which is similar to the result in our study 13 .…”
Section: Discussionmentioning
confidence: 99%
“…1,18 In reference to audit of requests from clinical departments, Obstetrics and Gynecology topped the table in claiming for maximum requests with an overall issue rate of 8,100 among which issue for PRBC with anemia as a common underlying indication. 15 Most of the cases had multiple transfusions leading to adverse reaction due to varied antigenic exposure and same is the factor for adverse reactions among females. Allergic reaction was the second highest prevalence of adverse reaction observed to be associated with transfusion and it is noted in 43 cases (0.2% of overall transfusion) presenting as urticaria and rashes.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 In the year 2012, "the Haemovigilance Programme of India" was commissioned by the Indian Pharmacopoeia Commission in collaboration with the National Institute of Biologicals under the auspices of Pharmacovigilance Programme of India, with an objective to track ATR due to transfusion of blood and its components in all affiliated blood banks across the country. 6,15 Hemovigilance system serving as a backbone of quality assurance, the present study was carried out with a novel aim of determining incidence of adverse transfusion-related reactions and to substantiate its patterns encountered in our teaching hospital blood bank located in remote South-Eastern part of the Country. The study owns an objective to enlighten knowledge and insights into patterns of ATR in the study domain which is not yet documented with special emphasis on root cause analysis with appropriate corrective and preventive actions.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were reported by Cheng and colleagues whereby they reviewed packed red blood cells (PRBC) cross-match requests and found inappropriate ordering was more pronounced for elective than emergency requests by 27.4% [ 30 ]. Several studies reported inappropriate requests among other blood components ranging from 22.2 to 42% [ 31 – 33 ]. All these studies show a large burden of inappropriate blood requests leading to unnecessary transfusions.…”
Section: Discussionmentioning
confidence: 99%